Geomagnetic dipole moment and Be-10 production rate intercalibration from authigenic Be-10/(9) Be for the last 1.3 Ma - Carcaillet, Jt; Bourles, Dl; Thouveny, N (Geochemistry, Geophysics, Geosystems, 2004)
A synthesis of authigenic Be-10/Be-9 ratio records constructed from sedimentary sequences deposited over the last 300 ka in the North East Atlantic and over the 500 - 1300 ka BP interval in the West Equatorial Pacific Ocean is compared with proxies of the geomagnetic moment variations over the same time intervals. These proxies consist in (1) relative paleointensity records obtained from the same sediments, (2) a seafloor magnetization record derived form magnetic anomalies, and (3) an absolute Virtual Dipole Moment (VDM) record constructed from an updated database of absolute paleointensities. The authigenic Be-10/Be-9 ratio records document the occurrence of the paleomagnetic events (excursions and reversals) reported for these time intervals by paleomagnetic studies. Reconstructions of Be-10/Be-9 derived magnetic moment records based on theoretical and empirical relationships between Be-10/Be-9 ratio and absolute VDM allow establishing Be-10 derived VDM records that exhibit the same overall structures as the geomagnetic proxy records.